In-situ grown of FeCo2O4 @ 2D-Carbyne coated nickel foam - A newer nanohybrid electrode for high performance asymmetric supercapacitors. (10th December 2022) - Dhandapani, Preethi; Balan, Balakrishnan; Dinadayalane, Tandabany; Angaiah, Subramania
Abstract: In this study, we synthesized 2D-carbyne by a simple chemical route coated on nickel foam. To this carbyne coated nickel foam, FeCo2 O4 was grown by the solvothermal process to serve as a nanohybrid electrode for asymmetric supercapacitor applications. This nanohybrid electrode has shown high specific capacitance due to the large surface area, high electrical conductivity and improved rate characteristics. The specific capacitance of FeCo2 O4 @Carbyne nanohybrid electrode was about 2584.8 Fg −1 at the current density of 3 Ag −1 . Furthermore, the asymmetric supercapacitor device assembled using FeCo2 O4 @Carbyne and activated carbon (FeCo2 O4 @Carbyne || AC) shows better performance with an energy density of about 93.12 Wh Kg −1 at a high-power density of 2.25 kW kg −1 with a capacitance decay of approximately 26 % even at 5000 cycles. These outcomes provide a new approach for the development of asymmetric supercapacitors with superior characteristics. Graphical abstract: Unlabelled Image Highlights: FeCo2 O4 @ Carbyne nanohybrid is a newer positive electrode material for asymmetric supercapacitors. FeCo2 O4 @ Carbyne nanohybrid delivers a specific capacitance of 2584.8 Fg −1 at the current density of 3 Ag −1 . FeCo2 O4 @ Carbyne || AC exhibits a high density of 96.59 Wh Kg −1 . The capacitance decay of 14.52 % is obtained at the high current density of about 10 Ag −1 .